Evaluation of suitability of different soybean varieties for cultivation in the conditions of the Central part of the Non-Chernozem region of the Russian Federation - A. A. Tevchenkov; Z. S. Fedorova (Аграрная наука Евро-Северо-Востока)
The article provides the data of the field experiment (2016-2019) on studying soybean varieties in order to determine their suitability for cultivation in Kaluga region (the central part of the Non-Chernozem region of the Russian Federation) and their use as a source of agronomic traits for further breeding work. The objects for the research were the soybean varieties of Russian (Mageva, Svetlaya, Kasatka, Maleta, Okskaya, Georgia) and Belarusian (Pripyat and Volma) breeding. Cultivation of soybean varieties in the northern regions of the country is limited due to the short growing season. During the research, the source of early ripening trait has been identified – Kasatka variety had the shortest vegetation period (109 days, 10 days less than Mageva standard variety). According to the plant height Pripyat (93.5 cm) and Okskaya (92.7 cm) varieties have been noted. In comparison to the control, Maleta, Pripyat and Volma varieties showed a steady dynamics towards dry matter accumulation increase. Plant yield index is the most important indicator in assessing soybean varieties genotype suitability for the certain cultivation area. A close correlation has been established between Svetlaya and Okskaya varieties yield indices and moisture availability indicators during the growing season (the amount of precipitation and the hydrothermal coefficient) (r = 0.9). The yield of the Belarusian Volma and Pripyat varieties showed a strong correlation between the average density and precipitation (r = 0.5-0.7) and HTC (r = 0.4-0.6), which proved the possibility of their cultivation in the Non-Chernozem region. On average over the research Pripyat variety has been the most productive one (2.0 t/ha, 21 % higher than the standard), which makes it useful as a source for increased productivity trait in soybean breeding.